Christopher Marlowe, Renaissance dramatist - Hopkins, Lisa (Renaissance dramatists, 2008)
Marlowe's life and death -- The Marlowe canon -- Marlowe on stage, 1587-2007: theatrical contexts and dramaturgical practice -- Marlowe as scholar: old and new knowledges in the plays -- Marlowe the horizon-stretcher: daring God out of heaven and conquering new worlds -- Critical issues